Efficacy of Ethyl Chloride Spray versus Subcutaneous 1% Lidocaine Injection for Relieving the Pain of One-rod Contraceptive Implant Removal: A single-blinded randomized controlled trial - Nartlada Mapaisankit; Pitch Chandeying; Sasikan Tangthasana (The Royal Thai College of Obstetricians and Gynaecologists, 2021)
Objectives: To evaluate the pain scores between using ethyl chloride spray and subcutaneous 1% lidocaine injection for relieving the pain from one-rod contraceptive implant removal.Materials and Methods: A total of 120 women who intended to remove the one-rod contraceptive implant were randomly assigned to receive ethyl chloride spray or 1% lidocaine injection before the procedure. Clinical characteristics including depth of implant, were collected. Pain during anesthetic administration, implant removal, and overall pain were evaluated using a visual analog scale (VAS). Participant and procedure assistant satisfaction were assessed. The outcome evaluator was blinded from the anesthetic method.Results: All patient characteristics were similar between two groups. Pain during anesthetic administration and overall pain in the ethyl chloride spray group was significantly lower than the lidocaine group (median VAS 0 and 3; p < 0.001 and median VAS 1 and 2.9; p < 0.001, respectively). However, pain during the procedure in the ethyl chloride spray group was found to be significantly higher compared to the lidocaine group (median VAS 1 and 0; p = 0.001). Implant removal duration in the ethyl chloride spray group was significantly shorter than the lidocaine group. Participant and procedure assistant satisfaction in the ethyl chloride spray group was significantly higher than the lidocaine group.Conclusion: Using ethyl chloride spray was effective for relieving the pain during anesthetic administration and overall pain of one-rod contraceptive implant removal. But it was associated with higher pain score during the procedure.